Navigating the Opportunities and Challenges of Health Information Technology in Modern Medicine - Indra Sandinirwan; Henry Leo (Syntax Corporation Indonesia, 2023)
The landscape of modern medicine has been significantly transformed with the advent of Health Information Technology (HIT). This wide-ranging field encompasses diverse technologies, from rudimentary charting mechanisms to advanced decision-support systems and integration with medical devices.1 A deeper understanding of the nuances of HIT provides a vista of opportunities for improving and transforming healthcare, potentially reducing human errors, enhancing clinical outcomes, and facilitating seamless care coordination. One of the uses of health information technology is electronic medical records. Electronic medical records (EMRs) have the potential to improve patient safety, but there are also concerns about safety issues related to their use. Some of the patient safety issues with EMRs include usability issues, such as poor information display and complicated screen sequences and navigation. Additionally, poor EHR interoperability can lead to increased risks of medication errors and other safety issues.2,3 However, EMRs can also improve the ability to diagnose diseases and reduce medical errors, improving patient outcomes.4 The role of EMRs in enhancing patient safety is still debated, and there is ongoing research to identify potential patient safety issues related to their use. The future of HIT, particularly EMRs, holds promising prospects for further revolutionizing healthcare delivery.